Penentuan Umur Simpan Yoghurt Sinbiotik Dengan Penambahan Tepung Gembolo Modifikasi Fisik - Ihsan, Rizqy Zainul; Cakrawati, Dewi (EDUFORTECH)
The study aim was to determine the shelf life of yogurt sinbiotik at several temperatures with the addition of Dioscorea esculenta modified flour. Lactic Acid Bacteria used for yoghurt making consist of Lactobacillus acidophilus, Bifidobacterium longun, Streptococcus themophillus. The method used Accelerated shelf life test (ASLT) with the characteristics observed namely pH, total acid value using titration method, and total lactic acid bacteria with TPC method. The concentration level of modified flour of Dioscorea esculenta was 2%. The shelf life of yogurt can be determined from the critical factor based on most rapid damage to the Arrhenius equation y = -3504,1x + 9.1043 and R2 = 0.5125. Yogurt sinbiotik stored at room temperature shelf life is 9.5 days. At 4 Â° C storage temperature, shelf life is 23.2 days. At 40 Â° C storage temperature, shelf life is 5.4 days. The addition of Dioscorea esculenta tuber starch in yogurt sinbiotik affect viability of LAB in the yogurt, since viability of lactic acid bacteria during storage has decreased, but the numbers are still within the range of CFU / ml on the final day of storageÂ